DAMPAK INVESTASI KOREA SELATAN DI PT KRAKATAU POSCO TERHADAP PEREKONOMIAN BANTEN - Dea Rizkiana Putri; Afrizal " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2016)
Indonesia is a commodity-based economic country that trying to change the economy based on industry and knowledge. Therefore the government of Indonesia trying to expand the industry sectors with increasing foreign direct investment in industry sectors, including steel industries. Among all of the foreign direct investment in steel industries, South Korea has the biggest investment for this sector. South Korea had a multi-billion dollar investment company in Indonesia which is a joint venture cooperation between POSCO and PT Krakatau Steel. POSCO is the world 4th biggest steel company from South Korea, PT Krakatau Steel is the South-East Asia Region 1st biggest steel company from Indonesia. The joint venture company, PT Krakatau Posco constructed in Banten, Indonesia. The result of this research shows the implication of the South Korea’s investment in PT Krakatau Posco towards economic development in Indonesia. It could be identified from some indicators, such as economic growth, employment and unemployment figures, and poverty level in Banten, Indonesia.Keyword: Implication, Foreign Direct Investment, Republic of Korea, PT Krakatau Posco, Indonesia, Banten.